Measurement and reporting of footwear characteristics in running biomechanics: A systematic search and narrative synthesis of contemporary research methods - Ramsey, C.; Peterson, B.; Hebert-Losier, K. (Sports Biomechanics, 2023)
This review aimed to synthesise the methods for assessing and reporting footwear characteristics among studies evaluating the effect of footwear on running biomechanics. Electronic searches of Scopus®, EBSCO, PubMed®, ScienceDirect®, and Web of Science® were performed to identify original research articles of the effect of running footwear on running biomechanics published from 1st January 2015 to 7th October 2020. Risk of bias among included studies was not assessed. Results were presented via narrative synthesis. Eligible studies compared the effect of two or more footwear conditions in adult runners on a biomechanical parameter. Eighty-seven articles were included and data from 242 individual footwear were extracted. Predominantly, studies reported footwear taxonomy (i.e., classification) and manufacturer information, however omitted detail regarding the technical specifications of running footwear and did not use validated footwear reporting tools. There is inconsistency among contemporary studies in the methods by which footwear characteristics are assessed and reported. These findings point towards a need for consensus regarding the reporting of these characteristics within biomechanical studies to facilitate the conduct of systematic reviews and meta-analyses pertaining to the effect of running footwear on running biomechanics.